2019
DOI: 10.1093/cdn/nzz122
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Depletion of Milk Exosomes and Their MicroRNA Cargos Elicits a Depletion of miR-200a-3p and Elevated Intestinal Inflammation and Chemokine (C-X-C Motif) Ligand 9 Expression in Mdr1a Mice

Abstract: Background Exosomes transfer regulatory microRNAs (miRs) from donor cells to recipient cells. Exosomes and miRs originate from both endogenous synthesis and dietary sources such as milk. MicroRNA (miR)-200a-3p is a negative regulator of the pro-inflammatory chemokine (C-X-C motif) ligand 9 (CXCL9). Male Mdr1a−/− mice spontaneously develop clinical signs of inflammatory bowel disease (IBD). Objectives We assessed whether dieta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 51 publications
1
37
0
Order By: Relevance
“…In another study, Mdr1a −/− mice with spontaneous inflammatory bowel disease were divided into two groups: the group fed with milk exosome-and RNA-sufficient (ERS) diet and the group fed with milk exosome-and RNA-depleted (ERD) diets. The study showed that the diet lacking bovine milk-derived exosomes caused miR-200a-3p depletion and elevated intestinal inflammation in Mdr1a −/− mice (Wu et al, 2019). Consistent with this finding, bovine milk-derived exosomes exhibited anti-inflammatory activity in a genetic mouse model of ulcerative colitis, as reported by Stremmel et al (2020).…”
Section: Milk-derived Evs and Immune Regulationsupporting
confidence: 78%
“…In another study, Mdr1a −/− mice with spontaneous inflammatory bowel disease were divided into two groups: the group fed with milk exosome-and RNA-sufficient (ERS) diet and the group fed with milk exosome-and RNA-depleted (ERD) diets. The study showed that the diet lacking bovine milk-derived exosomes caused miR-200a-3p depletion and elevated intestinal inflammation in Mdr1a −/− mice (Wu et al, 2019). Consistent with this finding, bovine milk-derived exosomes exhibited anti-inflammatory activity in a genetic mouse model of ulcerative colitis, as reported by Stremmel et al (2020).…”
Section: Milk-derived Evs and Immune Regulationsupporting
confidence: 78%
“…miRNAs from ginger‐derived VLNs, including miR‐159a, miR‐166u, and miR‐166p, have been shown to inhibit proliferation of a periodontal pathogen, Porphyromonas gingivalis (Sundaram et al., 2019). Ultrasonication of bovine skim milk leads to a >98% depletion of miRNAs in the milk EVs and a 20% depletion of milk EVs (Leiferman et al., 2018; Wu et al., 2019). When such ultrasonicated skim milk was supplemented in a mouse diet, the expressions of approximately 10 genes in skeletal muscle were altered, compared to mice fed with a diet supplemented with untreated skim milk (Leiferman et al., 2018).…”
Section: Discussionmentioning
confidence: 99%
“…When such ultrasonicated skim milk was supplemented in a mouse diet, the expressions of approximately 10 genes in skeletal muscle were altered, compared to mice fed with a diet supplemented with untreated skim milk (Leiferman et al., 2018). The same dietary depletion of milk EVs and their miRNA cargos elevated intestinal inflammation and altered transcription of 16 immune genes in Mdr1a –/– mice (Wu et al., 2019). However, it is not clear whether depletion of miRNAs in the milk EVs influences directly transcription in consumers or through other mechanisms (such as reshaping the microbiota in the gut).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Milk sEVs-derived RNAs can be absorbed by macrophages and intestinal cells in vitro [ 19 , 20 ], and can enter the circulatory system of milk consumers in vivo [ 21 ]. Recent research has shown that bovine milk exosomal miR-200a-3p is involved in alleviating cecal inflammation in mice [ 22 ].…”
Section: Introductionmentioning
confidence: 99%